2008
DOI: 10.1097/ta.0b013e31818a0e74
|View full text |Cite
|
Sign up to set email alerts
|

Early Venous Thromboembolism Prophylaxis With Enoxaparin in Patients With Blunt Traumatic Brain Injury

Abstract: Enoxaparin should be considered as an option for early VTE prophylaxis in selected patients with blunt TBI. Early enoxaparin should be strongly considered in those patients with TBI with additional high risk traumatic injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
79
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 25 publications
6
79
1
1
Order By: Relevance
“…Compliance rates in other studies range from 10% to 85%. 5,7,14,15,21 Minshall et al 13 intended chemoprophylaxis to begin at 24 hours after injury as well but had mean times to initiation of 47 hours for low-molecular-weight heparin and 54.8 hours for unfractionated heparin. Fifty percent of patients were started on chemoprophylaxis later than the 24 hours intended by Saadeh et al 21 In addition, Kim et al 10 and Depew et al 6 had 23% and 43% of patients, respectively, in whom chemoprophylaxis was initiated after their 72-hour protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compliance rates in other studies range from 10% to 85%. 5,7,14,15,21 Minshall et al 13 intended chemoprophylaxis to begin at 24 hours after injury as well but had mean times to initiation of 47 hours for low-molecular-weight heparin and 54.8 hours for unfractionated heparin. Fifty percent of patients were started on chemoprophylaxis later than the 24 hours intended by Saadeh et al 21 In addition, Kim et al 10 and Depew et al 6 had 23% and 43% of patients, respectively, in whom chemoprophylaxis was initiated after their 72-hour protocol.…”
Section: Discussionmentioning
confidence: 99%
“…2,9,11,16,20 Other studies have shown some efficacy of chemoprophylaxis in selected trauma patients with head injury. 1,14,15,21,22 Based on these studies, our trauma center adopted a new clinical protocol to initiate VTE chemoprophylaxis 24 hours following injury after demonstration of stable ICH verified by CT scan. We hypothesized that on review of our outcomes we would appreciate a decrease in the rate of DVT and pulmonary embolism (PE) without progression of ICH or development of a new hemorrhage on CT scan after implementation of the protocol.…”
mentioning
confidence: 99%
“…Evidence in a neurosurgical population indicates that pharmacological prophylaxis used in conjunction with mechanical devices is more effective than mechanical measures alone (Nurmohamed et al 1996;Agnelli et al 1998). Recent observational evidence suggests that initiation of prophylactic treatment w i t h L M W H w i t h i n 4 8 h o u r s o f i n j u r y o r n e urosurgical intervention is effective and associated with an acceptably low risk of complications (Norwood et al 2008;Dudley et al 2010). Unfortunately, the most effective agent and dosing strategy is yet to be determined.…”
Section: Principles Of Intensive Carementioning
confidence: 99%
“…66 For example, although still controversial, evidence suggests that early use of prophylactic anticoagulation is more beneficial than withholding this therapy in the TBI population. 67,68 Additional considerations include the effect of sedative agents on both hemodynamic and metabolic aspects of patient management. For example, the use of propofol for sedation may be associated with complications such as hypotension 69 , pancreatitis 70 , and propofol infusion syndrome.…”
Section: Pitfalls and Controversiesmentioning
confidence: 99%